THE SECOND SEMESTER STUDENTS’ ERRORS IN PRONOUNCING THE WORDS CONTAINING SILENT LETTERS - Alaka, Anta (Universitas Muhammadiyah Palembang, 2023)
This study was conducted to analyze of students’ pronunciation error toward English silent letters. The problems which should be answered in this study were silent letter errors which were made by students, and the factors that caused the errors. The objectives of this study were to find out silent letter errors made by the students and to know the factors that caused the error. The subject of this study was thirty two students of the second semester of Universitas PGRI Palembang. The technique of choosing the subjects was using purposive sampling. The method of this study was qualitative method. The data source of this study was student’s video recorder. The result of this study showed that there were eight silent letter errors made by students such as ‘B’, ‘C’, ‘H’, ‘L’, ‘P’, ‘T’, ‘U’, ‘W’. The dominant silent letters error made by the students were the letter ‘W” and ‘P’ with the highest percentage 100%. There were two factors that caused the error. Firstly, the students were lack of knowledge toward silent letters and phonetic transcription. Secondly, the students were accustomed to pronounce the wrong sound of the word.